First case report of Cyclosporiasis from eastern India: Incidence of Cyclospora cayetanensis in a patient with unusual diarrheal symptoms - Sardar, Sanjib K; Goel, Gaurav; Ghosal, Ajanta; Deshmukh, Rasika; Bhattacharya, Sanjay; Haldar, Tapas; Maruf, Md. Maimoon; Mahto, Rajkumar; Kumar, Jeevan; Bhave, Saurabh J; Dutta, Shanta; Ganguly, Sandipan (The Journal of Infection in Developing Countries, 2023)
Cyclospora cayetanensis, a recently described coccidian parasite causes severe gastroenteric disease worldwide. Limited studies are found on the incidence of C. cayetanensis infection from India; hence remains largely unknown. To date, no case of cyclosporiasis from eastern India has been reported. In this study, we described an incidental case of C. cayetanensis in a 30 years old Bengali female patient with no travel history from eastern India. In June 2022, the patient presented with a history of diarrhoea persisting for more than two months with continuous passage foul smelling stools for which she took multiple antibiotics that were ineffective. There were no Salmonella, Shigella, or Vibrio-like organisms in the patient's faecal sample, and Toxin A/B of Clostridium difficile was also not detected by ELISA. The patient was HIV-negative. Finally, UV autofluorescence and DNA-based diagnosis confirmed the presence of C. cayetanensis, and the treatment with a combination of appropriate antibiotics was successful. This case report could raise awareness about C. cayetanensis associated diarrhoeal cases in India.